A typological approach to grammaticalization and lexicalization East meets West - Xing, Janet Zhiqun (Trends in linguistics. Studies and monographs ;, 2020)
"Based on comparative analyses of diachronic data, the articles in this volume address both theoretical and methodological issues in the study of grammaticalization and lexicalization in both Eastern and Western languages. The central question raised and discussed in this volume is how, if any, typological properties of the two genetically unrelated language families interact with the processes of grammaticalization and lexicalization." --